2020
DOI: 10.1039/c9sm01627a
|View full text |Cite
|
Sign up to set email alerts
|

Loops versus lines and the compression stiffening of cells

Abstract: Both animal and plant tissue exhibit a nonlinear rheological phenomenon known as compression stiffening, or an increase in moduli with increasing uniaxial compressive strain. Does such a phenomenon exist in single cells, which are the building blocks of tissues? One expects an individual cell to compression soften since the semiflexible biopolymer-based cytoskeletal network maintains the mechanical integrity of the cell and in vitro semiflexible biopolymer networks typically compression soften. To the contrary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Furthermore, we have here used a rigid contractile body to model the cell. It would be interesting to study how mechanical feedback between the matrix and the cell emerges when the cell is itself modelled as a soft deformable object, for example, by treating the perimeter of the cell as a ring of springs that can stretch and bend ( Gandikota et al, 2020 ). In such cases the anisotropic force chains may lead to spontaneous polarization of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have here used a rigid contractile body to model the cell. It would be interesting to study how mechanical feedback between the matrix and the cell emerges when the cell is itself modelled as a soft deformable object, for example, by treating the perimeter of the cell as a ring of springs that can stretch and bend ( Gandikota et al, 2020 ). In such cases the anisotropic force chains may lead to spontaneous polarization of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…[61] VIF networks are soft but have an extraordinary ability to stiffen when under strain and can withstand much larger strains without breaking as compared to actin and microtubules. [61,62] A number of studies have now shown that VIFs modify the mechanical properties of the cell itself, enhancing the cell elastic behavior, [3][4][5]63] particularly under conditions of large cell strains [64,65] and in regions close to the perinuclear VIF network. [66] In the simplest physical picture, we can model the cytoskeleton as a spring with a spring constant k that is proportional to its stiffness.…”
Section: Vif Cytoplasmic Networkmentioning
confidence: 99%
“…Interestingly, recent modeling studies the phenomenon of compression stiffening in cells. Compression stiffening, a nonlinear rheological property in which a material’s moduli increase with increasing uniaxial compressive strain, has recently been discovered in static cells [85]. Such a phenomenon should also manifest itself in confined cell motility.…”
Section: Resultsmentioning
confidence: 99%